The potential of monitoring treatment response in non-small cell lung cancer using circulating tumour cells. (3rd August 2019) - Gallo, Marianna; De Luca, Antonella; Frezzetti, Daniela; Passaro, Valeria; Maiello, Monica R.; Normanno, Nicola
ABSTRACT: Introduction : Circulating tumor cell (CTC) counts represent an attractive strategy for monitoring response to therapy in patients with advanced non-small cell lung cancer (NSCLC). Changes in the CTCs number during the treatment have been proposed as a predictive biomarker of response to both chemotherapy and targeted therapies. Profiling of CTCs might also allow the assessment of the dynamics of predictive biomarkers such as EGFR, ALK, ROS1, and PD-L1, and provide relevant information in patients progressing on treatment with targeted agents including immunotherapeutics. Areas covered : A search of peer-reviewed literature in bibliographic databases was undertaken to discuss studies on CTCs and their predictive role in NSCLC. Expert opinion : To date, some challenges limit the clinical utility of CTCs in monitoring the response to treatment in NSCLC. The standardization of techniques for CTCs isolation and characterization and their validation on larger cohorts of patients might help to translate CTCs analysis in the clinic. However, studies on CTCs can provide information on molecular mechanisms involved in NSCLC progression and in the acquired resistance to treatments.